The Kosovo covenant - Kinđić, Zoran (Sociološki pregled, 2025)
One of the most important constituents of Serbian identity is the tradition about the Battle of Kosovo. Relying on Eliade’s distinction between the sacred and the profane, the author claims that for the Serbian people Kosovo is a sacred space, St Vitus’ Day is a sacred time, and Kosovo’s tradition is a sacred text. Thanks to the blood shed by Serbian knights who were martyrs for the defence of the Orthodox faith and the fatherland, the area of Kosovo has been transformed into a sacred space. St Vitus’ Day is a perpetual day in Serbian history because on that day Prince Lazar chose the Kingdom of Heaven on behalf on the entire nation of Serbs. The Kosovo Covenant is based on the previous Covenant of Saint Sava. Saint Sava and Saint Simeon the Myroblyte wanted to make Serbs the chosen people. The Kosovo Covenant was conceptualized by Danilo III, shortly after the Battle of Kosovo, whereas folk poetry spread through the Serbian people with that ideology. Thanks to this ideology, the Serbian people, although deprived of its state, succeeded in preserving its own identity.